2017
DOI: 10.18632/oncotarget.20242
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 5 gene polymorphism is associated with breast cancer susceptibility

Abstract: Toll-like receptor 5 (TLR5) plays a fundamental role in immune responses. Recent findings suggest the TLR5 expression level affects cancer progression and development. In the present study, our examination of 256 breast carcinomas specimens revealed that TLR5 is overexpressed in breast carcinomas, and that TLR5 overexpression correlated with lymph node metastasis and cancer grade (p<0.01). In a case-control study, we also analyzed associations between TLR5 single nucleotide polymorphisms (SNPs) and breast canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…cai et al (17) further reported that 80% of 75 cases of breast cancer expressed Tlr5, the majority of which were high-grade ductal carcinomas. Tlr5 was also overexpressed in 256 breast carcinomas specimens, and was correlated with lymph node metastasis and cancer grade (18). Furthermore, Berger et al (19) studied frozen breast specimens from 124 female patients with breast cancer and found that Tlr9 mrna expression was positively correlated with tumor grade, suggesting that Tlr9 may be a molecular marker for poorly differentiated breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…cai et al (17) further reported that 80% of 75 cases of breast cancer expressed Tlr5, the majority of which were high-grade ductal carcinomas. Tlr5 was also overexpressed in 256 breast carcinomas specimens, and was correlated with lymph node metastasis and cancer grade (18). Furthermore, Berger et al (19) studied frozen breast specimens from 124 female patients with breast cancer and found that Tlr9 mrna expression was positively correlated with tumor grade, suggesting that Tlr9 may be a molecular marker for poorly differentiated breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…They found that rs5744168 T allele encodes a stop at codon 392, affecting TLR5 signaling, and it is associated with sporadic breast cancer occurrence (OR > 1). On the other hand, they found no association between rs2072493 G allele and breast cancer risk [67]. Klimosch et al found that rs2072493 (A > G), nonsynonymous SNP coding for N592S is associated with colorectal cancer-specific and overall survival.…”
Section: • Potential Association Between Tlr4 Polymorphisms and Cancementioning
confidence: 99%
“… 5 According to a previous study, tumor biomarkers are associated with the tumorigenesis and progression of various cancers, such as breast cancer. 6 Therefore, there is a need to explore additional and convincing treatment drugs or tumor biomarkers to improve the efficacy of therapy in OTSCC patients.…”
Section: Introductionmentioning
confidence: 99%